2020
DOI: 10.1016/j.hjc.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease in women: Executive summary of the expert panel statement of women in cardiology of the hellenic cardiological society

Abstract: The perception that women represent a low risk population for cardiovascular (CV) disease (CVD) needs to be reconsidered. Starting from risk factors, women are more likely to be susceptible to unhealthy behaviors and risk factors that have different impact on CV morbidity and mortality compared to men. Despite the large body of evidence as regards the effect of lifestyle factors on the CVD onset, the gender-specific effect of traditional and non-traditional risk factors on the prognosis of patients with alread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 63 publications
0
4
0
1
Order By: Relevance
“…полученные статистически значимые различия (р<0,05) не противоречат логике и дизайну настоящей работы, а подтверждают общепризнанную концепцию м. dzau и e. вraunwald о сердечнососудистом континууме с развитием заболеваний ссс у женщин в более позднем возрасте [15,16]. основным фактором дестабилизации ссс у женщин в старшей возрастной группе в настоящий момент признается возрастные эндокринные изменения [17,18]. снижение уровня половых гормонов в результате возрастного угасания функции яичников вносит свой вклад в развитие аг в этот период в связи с потерей множественного (эндотелийзависимого и эндотелийнезависимого) «защитного» действия половых гормонов на ссс.…”
Section: материал и методыunclassified
“…полученные статистически значимые различия (р<0,05) не противоречат логике и дизайну настоящей работы, а подтверждают общепризнанную концепцию м. dzau и e. вraunwald о сердечнососудистом континууме с развитием заболеваний ссс у женщин в более позднем возрасте [15,16]. основным фактором дестабилизации ссс у женщин в старшей возрастной группе в настоящий момент признается возрастные эндокринные изменения [17,18]. снижение уровня половых гормонов в результате возрастного угасания функции яичников вносит свой вклад в развитие аг в этот период в связи с потерей множественного (эндотелийзависимого и эндотелийнезависимого) «защитного» действия половых гормонов на ссс.…”
Section: материал и методыunclassified
“…31,32 Although there are no significant sex differences in in-hospital mortality among patients with HFrEF, women with HFrEF are more symptomatic, with reduced 6-minute walk distances and a worse quality of life compared to men. 33,34 There is evidence that women with HFrEF have higher ejection fractions, smaller left atria, higher longitudinal strain and higher circumferential strain. 32,35,36 In contrast, another study showed no significant sex differences in LVEF.…”
Section: Heart Failure With Reduced Ejection Fractionmentioning
confidence: 99%
“…[ 31 , 32 ] Although there are no significant sex differences in in-hospital mortality among patients with HFrEF, women with HFrEF are more symptomatic, with reduced 6-minute walk distances and a worse quality of life compared to men. [ 33 , 34 ]…”
Section: Heart Failure With Reduced Ejection Fractionmentioning
confidence: 99%
“…2 Despite the increasing disease burden and associated morbidity and mortality, CVDs among women are often under-recognized, underdiagnosed, and eventually undertreated. 3 Furthermore, women remain significantly underrepresented in cardiovascular clinical research as compared to men. 4 This results in limited understanding of impact of CVD and the broad implications of various treatment modalities on women's health.…”
Section: Introductionmentioning
confidence: 99%